Follow-up Reality for Breast Cancer Patients – Standardised Survey of Patients and Physicians and Analysis of Treatment Data - Feiten, S.; Dünnebacke, J.; Friesenhahn, V.; Heymanns, J.; Köppler, H.; Meister, R.; Thomalla, J.; van Roye, C.; Wey, D.; Weide, R. (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: Currently, about 360 000 breast cancer patients who could, after completion of their primary therapy, take advantage of follow-up options are living in Germany. Up to now very little is known about the extent to which the available options are used and as to how the follow-up reality is experienced and evaluated. Thus, an explorative examination among the patients and their physicians was undertaken. Patients and Methods: All patients who underwent surgery in a certified breast centre between 2007 and 2013 received a standardised questionnaire; at the same time the physicians responsible for the follow-up were invited to answer a standardised questionnaire. Results: 920 patients (response rate: 61 %) with a median age of 65 years (32–95) could be analysed. 99 % of the participants stated that they regularly attended follow-ups. The personal contact with the physician (mean value: 4.4) and the reassurance that the cancer disease had not recurred (mean value: 4.5) were described on a scale of 0 to 5 to be two of the most important factors of the follow-up. Deficits were expressed with regard to psychosocial care (70 %) and the perception and treatment of physical complaints (55 %). In addition, 105 physicians returned completed questionnaires (response rate: 12 %). For asymptomatic patients the physicians performed the following examinations most frequently: anamnesis (92 %), physical examination (87 %) as well as laboratory tests (63 %) and tumour marker determinations (40 %). Conclusion: On the whole it became clear that the vast majority of the patients took advantage of the follow-up options. From the patientʼs perspective the importance of the follow-up lies in contact to the physician and the comforting assurance that the breast cancer has not relapsed. Deficits are seen in the psychosocial care and the perception and treatment of physical impairments. Not recommended examinations were employed by a significant proportion of the surveyed physicians.
Keywords: follow-up; breast cancer; survey; treatment data; guidelines